2015
DOI: 10.1007/s10517-015-2924-7
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Opioid Receptors to the Cytoprotective Effect of the Adaptation to Chronic Hypoxia at Anoxia/Reoxygenation of Isolated Cardiomyocytes

Abstract: We examined the role of opioid receptors in the cardioprotective effect of chronic continuous normobaric hypoxia in the model of anoxia/reoxygenation of isolated cardiomyocytes. Adaptation to hypoxia was provided by placing the rats for 21 days in an atmosphere with low O2 content. In intact rats, anoxia/reoxygenation of cardiomyocytes caused death of 23% cells and increased lactate dehydrogenase release from cardiomyocytes. In adapted rats, anoxia/ reoxygenation of cardiomyocytes caused death of only 2.5% cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Both effects were mediated via µ- and δ 2 -OR stimulation. We also found that CCH increased tolerance of isolated rat cardiomyocytes to anoxia/reoxygenation [ 61 , 107 ] . The cytoprotective effect of CCH was mediated by µ- and δ 2 -OR activation.…”
Section: The Mechanism Of the Myocardial Ischemic Tolerance Elicited ...mentioning
confidence: 99%
“…Both effects were mediated via µ- and δ 2 -OR stimulation. We also found that CCH increased tolerance of isolated rat cardiomyocytes to anoxia/reoxygenation [ 61 , 107 ] . The cytoprotective effect of CCH was mediated by µ- and δ 2 -OR activation.…”
Section: The Mechanism Of the Myocardial Ischemic Tolerance Elicited ...mentioning
confidence: 99%
“…CNH not only improves post-ischemic recovery Vol. 68 of heart function , but it also reduces myocardial infarct size (Maslov et al 2013, Chytilova et al 2015, Naryzhnaya et al 2015a and exerts cytoprotective effects against simulated ischemia/reperfusion in isolated cardiomyocytes (Borchert et al 2011, Naryzhnaya et al 2015b.…”
Section: Introductionmentioning
confidence: 99%